PENGARUH BIAYA PROMOSI TERHADAP PENINGKATAN JUMLAH MURID DI SEMPOA SIP SUMUT DAN ACEH - IVONE .; TRIANY WONGNUR; ARWIN .; LISA .; ELSERRA SIEMIN CIAMAS (LP2MTBM MAKARIOZ, 2019)
Formal education is a structured and tiered education pathway which consists of basic education, secondary education, andhigher education. Non-formal education is an education pathway out of formal education that can be implemented in astructured and tiered way. While, informal education is the path of family and environmental education (Law No. 20 of 2003).The formulation of the problem in this study is